Reading the room : group dynamics for coaches and leaders - Kantor, David (Jossey-Bass, A Wiley Imprint, 2012)
Praise for Reading the Room "If you believe, as I do, that tackling our toughest problems in organizations and societies will require significant advances in the human domain of how we think and interact, then you will find this book a wonderful resource for a healthier future."--Peter Senge, senior lecturer, leadership and sustainability, MIT Sloan School of Management; and founding chair, Society for Organizational Learning (SoL) "A must-read for anyone truly interested in gaining access to and managing their own actions/behavior as well as all those we work with, live with, and interact wi.